1992
DOI: 10.1002/cne.903250205
|View full text |Cite
|
Sign up to set email alerts
|

GAD‐ and GABA‐immunoreactivity in the ascending auditory pathway of horseshoe and mustached bats

Abstract: A comparative study of the immunostain to antibodies directed against glutamic acid decarboxylase (GAD) and gamma-aminobutyric acid (GABA) in the ascending auditory pathway was carried out in horseshoe bats (Rhinolophus rouxi) and mustached bats (Pteronotus parnellii). In both species GAD/GABA-positive puncta (presumed axonal boutons) and GAD/GABA-positive cells were found in the cochlear nucleus, the superior olivary complex, the nuclei of the lateral lemniscus the inferior colliculus, and the medial genicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 56 publications
7
84
0
Order By: Relevance
“…No signal was detected in rat brain sections incubated with the antibody (1:3,000) preabsorbed with recombinant rat GAD67 protein (180 μg/ml). Furthermore, the staining pattern of the antibody was consistent with that in a previous study (Vater, Kossl, & Horn, 1992). …”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…No signal was detected in rat brain sections incubated with the antibody (1:3,000) preabsorbed with recombinant rat GAD67 protein (180 μg/ml). Furthermore, the staining pattern of the antibody was consistent with that in a previous study (Vater, Kossl, & Horn, 1992). …”
Section: Methodssupporting
confidence: 89%
“…In the MSO of horseshoe and mustache bats, GABAergic neurons are sparsely present (Vater et al., 1992), while they are virtually absent in Japanese house bat (Ito et al., unpublished observation). Together, in horseshoe and mustache bats, MSO makes both excitatory and inhibitory influence on the IC in the same side, while in Japanese house bat it make excitatory influence on the bilateral IC.…”
Section: Discussionmentioning
confidence: 99%
“…The IC contains a significant proportion of GABAimmunoreactive cells which appear to encompass subclasses of disc-shaped and stellate cells (review: Oliver and Shneiderman 1991; horseshoe bat: Vater et al 1992b). Although direct evidence needs to be obtained, such cells could participate in local interactions within and across isofrequency laminae, thus contributing to inhibition observed at BF and in lateral sidebands of the tuning curves of single units.…”
Section: Possible Neuronal Substrates For Inhibitory Interactionsmentioning
confidence: 99%
“…In horseshoe bats, as in other mammals, the DNLL is composed of GABAergic projection neurons providing bilateral feedforward inhibition to the IC (cat: Adams and Mugnaini 1984;Shneiderman et al 1988;horseshoe bat: Vater et al 1990a). The intermediate nucleus and parts of the ventral nucleus of the lateral lemniscus and the LSO contain GABA-immunoreactive cell types which might include neurons projecting to the IC (Vater et al 1992b). Furthermore, the input from the contralateral IC (Schweizer 1981) might carry inhibitory components.…”
Section: Possible Neuronal Substrates For Inhibitory Interactionsmentioning
confidence: 99%
“…GABA, the main inhibitory neurotransmitter of the central nervous system (Sivilotti and Nistri, 1991), is also largely present in the auditory system. A number of investigators have shown that neurons, fibers, and terminals containing GABA or its synthesizing enzyme glutamic acid decarboxylase are present in auditory structures at every level from the cochlear nucleus to the thalamus (eg Adams and Mugnaini, 1984;Muganini and Oertel, 1985;Thompson et al, 1985;Wenthold et al, 1986;Peyret et al, 1986;Moore and Moore, 1987;Helfert et al, 1989;Dupont et al, 1990, Vater et al, 1992Wynne et al, 1995, Fubara et al, 1996, as well as in the auditory cortex (eg Winer, 1986).…”
Section: Introductionmentioning
confidence: 99%